Pengaruh Harga, Lokasi dan Word of Mouth Terhadap Minat Berkunjung Ke Kampung Cibarengkok - Dian Meliantari; Ari Apriani (Jurnal Kewarganegaraan, 2023)
Abstract Cibarangkok River Culinary Village is located in Cipeucang village, Cileungsi district, Bogor Regency. Tourist destinations that utilize river water flow as water tourism as well as to maintain the cleanliness of the river from garbage and maintain environmental sustainability. With the concept of inviting the surrounding community to participate in it, it is hoped that it can increase income for residents who manage culinary there. But not necessarily this tourist spot is visited by many people. So the way to make tourists come is accompanied by a fairly cheap entrance fee. The place is easy to find and close to the main highway adds positive value to this tourist spot. This research is to see and observe the influence of price, location and word of mouth on the intention to come to Cibarengkok Village. Using quantitative methods with a sample of 80 people through questionnaires. Results were processed by multiple linear regression using the SPSS 26 application. As a result, individual prices have no real impact on the intention to come to Cibarengkok village. While the Tourism Location and Word of Mouth results have a very real effect on the intention to visit Cibarengkok Village. Simultaneously, price, location and word of mouth have a real effect on the interest in visiting Cibarengkok village. Keywords: Creative Economy, Green Economy, Cibarengkok Village, Post-Pandemic Abstrak Kampung Kuliner Kali Cibarangkok berada di desa Cipeucang kecamatan Cileungsi Kabupaten Bogor. Destinasi wisata yang memanfaatkan aliran air sungai sebagai wisata air sekaligus untuk menjaga kebersihan sungai dari sampah serta menjaga kelestarian lingkungan. Dengan konsep mengajak masyarakat sekitar untuk turut berpartisipasi di dalamnya diharapkan dapat menambah penghasilan bagi warga yang mengelola kuliner di sana. Tetapi tidak serta merta tempat wisata ini banyak dikunjungi orang. Maka jalan untuk membuat wisatawan datang adalah diimingi dengan biaya tiket masuk yang cukup murah. Tempatnya mudah ditemui dan dekat dengan jalan raya utama menambah nilai positip bagi tempat wisata ini. Riset ini untuk melihat dan mengamati pengaruh harga, lokasi dan word of mouth pada niat datang ke Kampung Cibarengkok. Menggunakan metode kuantitatif dengan sampel sebanyak 80 orang melalui pemberian kuesioner. Hasil diolah dengan regresi linier berganda memakai aplikasi SPSS 26. Hasilnya, Harga secara individu tidak berdampak nyata terhadap niat datang ke kampung Cibarengkok. Sedang Lokasi Wisata dan Word of Mouth hasilnya berpengaruh sangat nyata terhadap niat mengunjungi Kampung Cibarengkok. Secara simultan harga, lokasi dan word of mouth berpengaruh nyata pada minat berkunjung ke kampung Cibarengkok. Kata Kunci: Ekonomi Kreatif, Ekonomi Hijau, Kampung Cibarengkok, Pasca Pandemi